PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE NHT BERBANTUAN FLIPBOOK TERHADAP HASIL BELAJAR SISWA PADA MATERI VIRUS - Nopianingsih, Sri; Ariyati, Eka; Marlina, Reni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe research aimed to determine the effect of the cooperative learning model  numbered heads together type assited by flipbook on student learning outcomes in the material of virus in class X SMA Muhammadiyah 1 Pontianak. The study was a quasy experimental research with a nonequivalent control group design. The sampling technique used intact group with class X-MIA-3 as the experimental class and class X-MIA-2 as the control. The instrument was in the form of a multiple choice test with 20 items. The average learning outcomes of exsperimental class which was 15,26 while the average in control class was 11,60. The results of U Mann-Whitney test showed that Zcount(-3,67) < -Ztable (-1,96), meaning that there were significant differences between the learning outcomes of students taught using cooperative learning model numbered heads together type assited by  flipbook and conventional model. The effect size value obtained was 0,87 with a high category and gave the effect of 30,78%.   Keywords: Effect, Cooperative Learning Model  Numbered Heads Together Type Assited By Flipbook, Learning Outcomes, Virus